Nodular fasciitis on chest wall in a teenager: a case report and review of the literature - Suh, Jong Hui; Yoon, Jeong Seob; Park, Chan Beom (Journal of Thoracic Disease, 2014)
We report the case of a 16-year-old boy with a rapid growing mass on his left anterior chest wall. The mass was completely resected, and pathological examination confirmed nodular fasciitis. Benign chest tumors rarely occur in childhood. Nodular fasciitis is a benign proliferation of myofibroblast that is often mimicked by a sarcoma of the soft tissue. Physicians should consider the possibility of nodular fasciitis in chest wall tumors in the pediatric population.